2020
DOI: 10.1111/bcp.14632
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial‐protective effects of a G‐protein‐biased sphingosine‐1 phosphate receptor‐1 agonist, SAR247799, in type‐2 diabetes rats and a randomized placebo‐controlled patient trial

Abstract: agonist designed to activate endothelial S1P 1 and provide endothelial-protective properties, while limiting S1P 1 desensitization and consequent lymphocyte-count reduction associated with higher doses. The aim was to show whether S1P 1 activation can promote endothelial effects in patients and, if so, select SAR247799 doses for further clinical investigation. Methods: Type-2 diabetes patients, enriched for endothelial dysfunction (flowmediated dilation, FMD <7%; n = 54), were randomized, in 2 sequential cohor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 86 publications
(121 reference statements)
6
13
4
Order By: Relevance
“…Indeed, we showed in the present study in Ob-ZSF1 rats, that SAR247799, through its mechanism of action on endothelial function, reduced VLF bands of systolic blood pressure variability, an index of endothelial nitric oxide pathway activation (23). Similarly, our previous work shows that SAR247799 improves coronary microvascular reserve in a pig model of ischemic injury (15) and endothelial and renal function in diabetic rats (16). Furthermore, SAR247799 improves flow-mediated dilation in type-2 diabetes patients (16).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Indeed, we showed in the present study in Ob-ZSF1 rats, that SAR247799, through its mechanism of action on endothelial function, reduced VLF bands of systolic blood pressure variability, an index of endothelial nitric oxide pathway activation (23). Similarly, our previous work shows that SAR247799 improves coronary microvascular reserve in a pig model of ischemic injury (15) and endothelial and renal function in diabetic rats (16). Furthermore, SAR247799 improves flow-mediated dilation in type-2 diabetes patients (16).…”
Section: Discussionsupporting
confidence: 79%
“…Effects of SAR247799 on physiological parameters SAR247799 was incorporated in the chow at the dose of 250 mg/kg as a previous study from our laboratory demonstrated the effect of this dose in endothelial protection in another rat model of metabolic dysfunction (16). In this study, the plasma concentration of SAR247799 after weeks of treatment was 7-fold higher in young compared to the old ZSF1 rats.…”
Section: 8mentioning
confidence: 63%
See 2 more Smart Citations
“…This compound is a G protein-biased selective S1P 1 agonist that activates the G i/0 pathway more potently than the β-arrestin recruitment and S1P 1 internalization [87]. Therefore, the compound will activate S1P 1 without receptor desensitization and lymphocyte depletion [87,88]. Regarding renal Epo production, it would be very interesting to see whether this compound can stimulate Epo production in a more long-term situation.…”
Section: Discussionmentioning
confidence: 99%